CULTIVATING DISCIPLINE IN STUDENTS THROUGH REWARDS AND PUNISHMENT - Hanifah Rahmi; Kasuwi Saiban; Umi Salamah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This study aims to analyze the implementation of reward and punishment in instilling discipline among students. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldana, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of rewards in the form of praise, gifts, and appreciation was able to improve students’ learning motivation, compliance with regulations, and enthusiasm in participating in boarding school activities. Meanwhile, educational punishments, such as warnings, additional assignments, and restriction of certain facilities, proved effective in controlling behavior and reducing disciplinary violations among students. The balanced implementation of reward and punishment was able to create an orderly and conducive boarding school environment while supporting the development of responsibility, independence, and discipline among students. This study also found that the implementation of reward and punishment has implications for character building and the development of a disciplinary culture within the boarding school environment. However, when applied excessively and disproportionately, rewards may lead to dependency and decrease students’ intrinsic motivation. Therefore, a wise, educational, and sustainable strategy in implementing reward and punishment is needed so that the process of developing students’ discipline can be carried out optimally. The research results show that the balanced implementation of rewards and punishments has a positive impact on increasing student learning motivation, compliance with regulations, and reducing disciplinary violations. Furthermore, this policy contributes to creating an orderly and conducive Islamic boarding school environment and strengthening the character development of responsibility, independence, and a culture of discipline among students. However, excessive implementation of rewards has the potential to create dependency and reduce students' intrinsic motivation, so proportional, educational, and sustainable implementation is needed.